Cytoskeletal Remodeling Mimics Endothelial Response to Microgravity - Locatelli, Laura; Maier, Jeanette A. M. (Frontiers in Cell and Developmental Biology, 2021)
Mechanical cues contribute to the maintenance of a healthy endothelium, which is essential for vascular integrity. Indeed endothelial cells are mechanosensors that integrate the forces in the form of biochemical signals. The cytoskeleton is fundamental in sensing mechanical stimuli and activating specific signaling pathways. Because the cytoskeleton is very rapidly remodeled in endothelial cells exposed to microgravity, we investigated whether the disruption of actin polymerization by cytochalasin D in 1g condition triggers and orchestrates responses similar to those occurring in micro- and macro-vascular endothelial cells upon gravitational unloading. We focused our attention on the effect of simulated microgravity on stress proteins and transient receptor potential melastatin 7 (TRPM7), a cation channel that acts as a mechanosensor and modulates endothelial cell proliferation and stress response. Simulated microgravity downregulates TRPM7 in both cell types. However, 24 h of treatment with cytochalasin D decreases the amounts of TRPM7 only in macrovascular endothelial cells, suggesting that the regulation and the role of TRPM7 in microvascular cells are more complex than expected. The 24 h culture in the presence of cytochalasin D mimics the effect of simulated microgravity in modulating stress response in micro- and macro-vascular endothelial cells. We conclude that cytoskeletal disruption might mediate some effects of microgravity in endothelial cells.